Learning Tajwid and Murottal Al-Qur'an Science for Children in Wirakanan Village, Wirakanan Village, Kandanghaur District - Ahmad Kurnia (Annujum: Journal of Humaniora and Law, 2025)
Developing village potential towards a progressive society is something that must be considered. Students are expected to be able to understand every problem that occurs in society and make the best decisions to solve these problems with creative ideas. One form of student contribution in improving the quality of society is by carrying out community service programs. "Learning the Science of Tajwid and Murottal Al-Qur'an for Children" is one of the titles of the Community Service Support Program which will be implemented in Wirakanan Village. The aim of implementing this program is to increase understanding of how to read the Al-Qur'an using Murottal songs and provide an understanding of the sciences of recitation and increase understanding of Makhorijul Letters for children in Wirakanan Village. This program uses several methods such as lecture, demonstration and question and answer methods. For example, when using the lecture method, each student is expected to be able to listen and understand the material presented by the educator so that the material presented can be absorbed optimally. Likewise with the demonstration method, educators practice the material to be delivered, then students listen and understand and then practice what has been conveyed by the educator. Meanwhile, the question and answer method is used when teaching and learning activities take place and there are students who do not understand, so students are invited to ask questions and the teacher will answer. Not only asking questions to educators, but students are able and allowed to ask other students so that active interaction occurs during the learning process. By holding this program, we hope that children in Wirakanan Village can understand and practice the science of recitation when reading the Koran and being able to recite it. The results of the activities obtained from the work program are: (1) Children understand and comprehend the material that has been presented regarding Tajwid Law and Makhorijul Letters. (2) Children can practice the knowledge of Tajwid and Makhorijul Letters when reading verses of the Koran. (3) Children begin to understand and apply reading the Al-Qur'an using Murottal Al-Qur'an.